Transesophageal Echocardiography in an Adult Patient With Double-Chambered Right Ventricle. Issue 3 (1st February 2019) - Grossi, Raphael; Béïque, François; Hatzakorzian, Roupen; Codère-Maruyama, Takumi; Schricker, Thomas; Villeneuve, Valérie
Abstract : Supplemental Digital Content is available in the text.